How workers learnt chemistry - Anderson, Robert G.W. (Circumscribere International Journal for the History of Science, 2014)
Most of the time when historians study chemistry the subject dealt with is what might be called élite chemistry. This is chemistry at the cutting edge, chemistry which makes a difference to how we come to understand the properties of matter, molecules, reactions, and so on. Other associated matters which may be explored by historians of chemistry concern social, economic or political relationships with élite chemistry. In this Debus Lecture I want to consider what possibilities there were that the working-class would be able to learn about chemistry in the earlier part of the nineteenth century, and how and why this was achieved.